2017
DOI: 10.1371/journal.pone.0179366
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human cytomegalovirus in glioblastoma among Taiwanese subjects

Abstract: The relationship between human cytomegalovirus (HCMV) and glioblastoma (GBM) has been debated for more than a decade. We investigated the presence of HCMV genes, RNA and protein in GBMs and their relationships with tumor progression. Results of quantitative PCR for HCMV UL73, nested PCR for HCMV UL144, in situ hybridization (ISH) for RNA transcript, and immunohistochemistry (IHC) for protein expression and their relationship to the prognosis of 116 patients with GBM were evaluated. Nine (7.8%) cases revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…However, this link between CMV and tumor progression is far from clear. Several clinical studies have failed to identify HCMV in human tumors, even with the use of very sensitive molecular techniques (54)(55)(56)(57). Moreover, several studies suggest that CMV may have the opposite effect and block tumor growth in other experimental situations.…”
mentioning
confidence: 99%
“…However, this link between CMV and tumor progression is far from clear. Several clinical studies have failed to identify HCMV in human tumors, even with the use of very sensitive molecular techniques (54)(55)(56)(57). Moreover, several studies suggest that CMV may have the opposite effect and block tumor growth in other experimental situations.…”
mentioning
confidence: 99%
“…Literatures that met the following criteria were excluded: (1) the written language was not English, (2) reviews, letters, editorials, and meeting records, (3) study focusing on gene expression, (4) the detection samples were not from the glioma samples of the patients, (5) neither the viral antigen nor DNA were detected, and (6) sample cases were from a database.…”
Section: Eligibility Criteria and Quality Assessmentmentioning
confidence: 99%
“…2018)[4],(Yang et al 2017)[5],(Bahador et al 2017)[6],(Ding et al 2014)[7], (Rahbar et al 2013)[8], and (Rahbar, a. et al 2012)[9] ; 2 studies involved HPV: (Adnan Ali et al 2019)[10], (Vidone et al 2014)[11] and (Wang et al 2017)[14]; 2 studies involved HHV-6: (Crawford et al 2009)[12] and[13]; and 1 study involved SV40, WMSV and HERV-K113:(Wang et al 2017) …”
mentioning
confidence: 99%
“…No viral detection by day 7 post-challenge in brains and lungs (HA)-MCMV IVL [35] IN route induced lung CD8 TRM accumulation IAV PR8M variant IN challenge MHC-I restricted peptide IVL [533][534][535][536][537][538][539][540][541] Inserted into the C-terminus of the ie2 IN reduced lung viral load and weight loss at a higher magnitude than IP route MCMV ie2E6/E7Full [14] Protective CD8 T cells Heterotopic (subcutaneous) administration of TC-1 cells transformed with HPV16 E6 and E7-oncogenes cells [59] and subsequent development of an immunosuppressive microenvironment [60] partially overlap with phenomena promoting the immune evasion by cancer cells [61]. Some clinical studies have suggested a role for CMV in the pathogenesis of glioblastoma, an aggressive neoplasm of the central nervous system [62,63] but subsequent studies have shown conflicting results concerning HCMV identification in tumours [64][65][66][67][68], a fundamental requisite according to the criteria proposed by Frederick and Relman for the identification of diseases caused by viruses [69,70]. Therefore, a consensus to consider CMV as an oncogenic virus or merely an oncomodulatory virus that may cause tumour cells to become more aggressive has not been reached [71].…”
Section: Mouse-adapted Zebov Ip Challengementioning
confidence: 99%
“…Advantages of using a full-length protein include the elicitation of broad immune responses in various MHC backgrounds which increases the prospect of a protective response toward critical epitopes in genetically heterogeneous populations [149]. A comparison of MCMV-based vectors encoding either the full length gene of the prostate-specific antigen (PSA) (MCMV/PSA FL ) or a PSA-derived epitope (MCMV/PSA [65][66][67][68][69][70][71][72][73] ) within the ie2 gene [150] showed that only MCMV/PSA [65][66][67][68][69][70][71][72][73] protected against tumour challenge with a PSA-expressing adenocarcinoma, although both vectors induced an inflationary response of PSA-specific CD8 T cells. As MCMV/PSA FL induced poor CD8 response upon challenge, the mechanism of CD8 suppression was suspected to depend on differences in the functionality of responding cells.…”
Section: Cellular Response-t Cellsmentioning
confidence: 99%